Radial incision and cutting combined with balloon dilation for refractory pancreaticojejunostomy anastomotic strictures - Inoue, Tadahisa (Endosc Int Open, 2021)
Background and study aims  Endoscopic balloon dilation (BD) and temporary stent placement for pancreaticojejunostomy anastomotic stricture (PJAS) achieves good short-term outcomes; however, stricture recurrences remain frequent. We examined the feasibility of performing radial incision and cutting (RIC) combined with BD for refractory PJAS. Patients and methods  Five consecutive patients with refractory PJAS who underwent RIC with BD between 2015 and 2018 were retrospectively investigated. We evaluated the technical and clinical success, adverse event (AE), and recurrence rates associated with RIC with BD. Results  In all five patients, technical and clinical success were achieved. Pancreatic stone removal was simultaneously performed in one patient. The mean procedure time was 18 minutes (range 12–23 minutes). There were no procedure-related AEs. All patients were followed for over 2 years, with a mean follow-up period of 33 months (range 24–40 months). During the follow-up period, none of the patients developed stricture recurrence and all anastomoses remained patent. Conclusions  This is the first report of RIC with BD for the treatment of refractory PJAS, showing favorable results. This combined procedure might be a useful option for treating refractory PJAS.